Moving Beyond the Momentum: Innovative Approaches to Clinical Trial Implementation. Issue 10 (October 2021) - Eng, Cathy; Chen, Emerson Y.; Rogers, Jane; Lewis, Mark; Strosberg, Jonathan; Thota, Ramya; Krishnamurthi, Smitha; Oberstein, Paul; Govindarajan, Rang; Buchschacher, Gary; Patel, Sandip; Sohal, Davendra; et al.
Abstract : Despite efforts to enhance enrollment and the merger of national cooperative groups, < 5% of patients with cancer will enroll into a clinical trial. Additionally, clinical trials are affected by a lack of diversity inclusive of minority patients, rural residents, or low-income individuals. COVID-19 further exacerbated known barriers of reduced physician-patient interaction, physician availability, trial activation and enrollment, financial resources, and capacity for conducting research. Based on the cumulative insight of academic and community clinical researchers, we have created a white paper identifying existing challenges in clinical trial conduct and have provided specific recommendations of sustainable modifications to improve efficiency in the activation and conduct of clinical trials with an overarching goal of providing improved access and care to our patients with cancer.